Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Let $(f_n)_{n \in \mathbb{N}}$ a sequence of function from a nonempty-set $X$ to $\bar{\mathbb{R}}=[-\infty,\infty]$, $g\colon X \to \bar{\mathbb{R}}$ defined by $g(x)=\sup_{n \in \mathbb{N}} f_n (x)$. Then $$g^{-1}\bigl( (a,+\infty] \bigr)=\bigcup_{n \in \mathbb{N}} f_n^{-1}\bigl((a,+\infty]\bigr).$$ Why?

share|improve this question
    
You are doing Tao 18.5.10 ? That was my reason for searching for that :D –  André Dec 30 '12 at 15:08

1 Answer 1

up vote 2 down vote accepted

Note that $$\begin{align*} x\in g^{-1}\bigl( (a,+\infty] \bigr)&\iff g(x)\in(a,+\infty]\\\\ & \iff\sup_{n\in\mathbb{N}}\;f_n(x)\in(a,+\infty]\\\\ *&\iff\exists\,n\in\mathbb{N}\text{ such that }f_n(x)\in(a,+\infty]\\\\ &\iff\exists\,n\in\mathbb{N}\text{ such that }x\in f_n^{-1}\bigl((a,+\infty]\bigr)\\\\ &\iff x\in\bigcup_{n\in\mathbb{N}}f_n^{-1}\bigl((a,+\infty]\bigr) \end{align*}$$ The step labeled $\ast$ is the key step; if we had chosen to look at $[a,+\infty]$, instead of $(a,+\infty]$, it would be false. We need that $$\sup\; a_n>b\iff \lnot(\sup\; a_n\leq b)\iff\lnot(a_n\leq b\text{ for all }n\in\mathbb{N})\iff a_n>b\text{ for some }n\in\mathbb{N}.$$

Thus, we have shown that $$g^{-1}\bigl( (a,+\infty] \bigr)=\bigcup_{n \in \mathbb{N}} f_n^{-1}\bigl((a,+\infty]\bigr).$$

share|improve this answer

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.